Inclusive growth: The case of Germany - Günther Schmid (Institute of Labor Economics (IZA), 2018)
This paper argues that inclusive growth appears to be the only suitable strategy for realising the right to decent work (RDW) in the digital economy. This reasoning is in blunt opposition to the current mood of giving up this right in favour of an unconditional basic income (UBI). The study starts by briefly expanding the basic argument and by defining the principles of inclusive versus exclusive growth (1); a comprehensive overview of German labour market policy and labour law reforms since the beginning of this millennium assesses to what extent Germany is pursuing these principles, accompanied by selective evidence of their consequences for the German labour market performance (2); a stylised and descriptive overview of the inclusive impact of these reforms in quantitative and qualitative terms follows, with an essay reflecting the concept of the inclusive labour contract (3).
Keywords: J41; J48; K31; K38; O43; R11; 330; labour market policy; labour law; human right law; inclusion; institutions; growth; non-standard work; Germany